PERANAN NOTARIS DALAM PEMBUATAN KETERANGAN HAK WARIS BAGI GOLONGAN TIONGHOA (Studi Kasus : Kantor Notaris DENPASAR) - Angelina Sunarto, Hanatasia; Astariyani, Ni Luh Gede (Kertha Semaya : Journal Ilmu Hukum, 2013)
The certificate of inheritance in Indonesia made by different agencies according to theclasses of people penduduk.Bagi Chinese Foreign Orientals, heir certificate Notary. For theChinese Foreign Orientals than among Arabs, heir certificate created by Heritage Hall, andfor indigenous groups, a statement made by the heirs of the heirs on paper stamped and thenknown by the village chief / head of village and district head quarters last heir at the time ofdeath. The certificate of inheritance different for each population group due to theclassification of population under Article 131 IS. Classification of the residents of a politicallegacy of Dutch law. Officials who make the notary as a Certificate of Inheritance for theChinese, must pass through several stages in order to issue a Certificate of Inheritance.Based on the above conditions, it can be formulated some problem formulation, ie Is theefforts made to obtain information about the Notary presence or absence of the deceased'swill left by the Register center Testament (DPW), and How-making process in the NotaryCertificate of Inheritance for Group Chinese in Notaries / PPAT Inti Sariwati. The Titel ofthis article is Notary Role in Making a Statement to the class Inheritance Tionghoa. Inwriting this journal juridical approach used empirical, and legal materials were processedby using qualitative data processing techniques. In an effort received a Certificate of RegisterCentre Wills, Notary must submit notarized identity of the deceased, among other things, thedeath certificate, family card, ID card, and the establishment of an Indonesian citizen. After 2months, the notary will receive the certificate, and then will prepare a Notary Deed andSpecification testimony to be read before the husband or wife of the deceased, and also 2witnesses who know the true life of the deceased during his lifetime. In conclusion, in order toreceive a certificate, a notary will take approximately two months, because the system is stillmanual, and Notary issued a Certificate of Inheritance based on statements and testimonygiven by the husband or wife of the deceased and also the witnesses who are familiar with thedeceased during his lifetime.
Keywords: Notaries, Certificate of Inheritance, Register Centre Testament